Comparison of chemo-mechanical and conventional caries removal methods in 6-to-12-year-old children: Randomized clinical trial - Abdulrahman Bala Malami; Yewande Isabella Adeyemo; Aliyu Aminu; Folakemi Adenike Oredugba (PLoS ONE, 2026)
Background To address the discomfort associated with conventional drilling for caries removal in children, a minimally invasive approach such as chemo-mechanical caries removal was developed. This study aimed to compare the effectiveness of, and patient behavior associated with chemo-mechanical caries removal versus conventional drilling in children aged 6–12 years. Methods A split-mouth randomized clinical trial was conducted involving 66 molar teeth. The effectiveness of Papacarie Duo Gel and conventional drilling methods was assessed using colony-forming unit (CFU) counts before and after each treatment. Cavity preparation time and intraoperative patient behavior using the Frankl Behavior Rating Scale were also evaluated. Results Both methods resulted in a significant reduction in bacterial counts post-treatment. However, conventional drilling showed a greater percentage reduction in bacterial load (82.9 ± 13.9; t = −4.42, p < 0.001) compared to the chemo-mechanical method (68.6 ± 16.6). The mean caries removal time was 692.4 ± 245.9 sec with the chemo-mechanical method, compared to 266.9 ± 101.6 sec with conventional drilling. In terms of behavior, 57.6% of the children exhibited a positive response during chemo-mechanical treatment whereas negative behavior was more commonly observed with conventional drilling. Conclusion While conventional drilling remains the better-established and time-efficient method of caries removal, the chemo-mechanical technique serves as a valuable alternative for managing children, reducing anxiety and promoting greater comfort and cooperation during treatment. Trial registration PanAfrican Clinical Trial Registry PACTR202310877678533